PERAN PEREMPUAN DALAM INDUSTRI KECIL(STUDI KASUS PEREMPUAN BEKERJA PADA INDUSTRI KECIL PENGRAJIN MANIK-MANIK DI DESA PLUMBON GAMBANG KECAMATAN GUDO KABUPATEN MALANG - Wisadirana, Darsono; Dewi, Ratih Kusula (Jurnal Interaktif, 2011)
This research is based on phenomenon of women worker on small industry of Beads Artwork at Plumbon Village Gambang Gudo Sub district Jombang District which is considered as social reality which is a frequently seen in Indonesia. The problems of this research are how the gender deferential work in small industry of Beads Artwork and how womenâs role in this small industry. The aims of this research to know women role in small industry ofÂ  Beads Artwork which is observed through the women involvement, time allocation, and the decision making pattern.The research uses study case method with qualitative approach. This research uses purposive sampling and the technic of data collecting such as indepth interview with respondens, observation, and documentation.The result of this research shows that in unit industry of Beads Artwork, women workers are very identical with simple jobs, unrisky jobs, jobs which are not far from home and jobs which requiring patience. Mean while the men workers get the jobs which are contrast to the women workers. The men workers are very identical with jobs requiring strength which need physical force with high risk and high skill. The men workers are mostly being involved in production process such as frying pan, cleaning, colloring, smelting, obstruction making and making of Beads. While the women workers are mostly being involved in choosing material process, cleaning asbes, choosing and making the Beadsâ structure. Men and women have nearly same time allocation in the small industry that is about 8 hours everyday.In the task of decision making such as in the activities of buying raw materials, deciding the amount of raw materials as well as deciding the place to buy the materials, not women and men are involved together. However, the women are more dominant in the activity of buying materials. While men are more dominant in selling and marketing the products. Key words: Role, small industry, gender, time allocation, and decision making.